Cultural Beliefs and Mental Health - Boltivets, Sergii (Journal of Psychosociological Research in Family and Culture, 2023)
The intersection of cultural beliefs and mental health is a critical area of study, particularly as our societies become increasingly multicultural. Cultural beliefs significantly influence how individuals perceive mental health, seek treatment, and respond to interventions. This article explores the intricate relationship between cultural beliefs and mental health, highlighting recent research and implications for practice and policy. Cultural beliefs profoundly influence mental health perceptions, care, and treatment. Understanding these beliefs is essential for providing effective and culturally sensitive mental health services. As our societies become more diverse, it is imperative to integrate cultural competence into mental health policies, practices, and education. By doing so, we can ensure that mental health care is inclusive, equitable, and responsive to the needs of all individuals, regardless of their cultural backgrounds.